Pengaruh Pendidikan Kesehatan Perawatan Kaki Diabetik dengan Metode Demonstrasi Terhadap Kemampuan Merawat Kaki Pada Pasien Diabetes Mellitus - Rina Sari Dewi Setyaningsih; Arina Maliya (Universitas Muhammadiyah Surakarta, 2018)
The disease of DM complications often form of stroke, kidney failure, heart, nephropathy, blindness and even had to undergo amputation. The problem of diabetes leg injury in Indonesia to date is still a complex issue, because the mortality rate and the amputation is still high. One of the treatment DM was with education. Research objectives to find out the influence of health education against diabetic foot treatment with the method of demonstration in diabetics mellitus patients. The research was included in this type of Pre-experimental design with Intact-Group Comparison approach. Enginering samples are non probability sampling with technical purposive sampling of as many as 30 respondents. The average level of knowledge prior to health education is 12.766 and after extension or increased 15,166 better. The ability of people with diabetes mellitus care for leg before given health education the average rating is 4,666 and the ability of people with diabetes mellitus in taking care of feet after a given health education with an average 8,133. The summary is the influence of health education against diabetic foot treatment with demonstration methods can improve the care of diabetic foot as much as 3,466 from before the demonstration.